The Lexical Concept of ‘Negeri’ in Malay Proverbs: An Inquisitive Semantic Study - Siti Andriana; Rahmi Septia Frisye; Hermandra (Raja Zulkarnain Education Foundation, 2026)
This study employs an inquisitive semantics approach, which remains relatively underutilized in linguistic studies in Indonesia. To date, research on Malay proverbs has tended to focus on the classification of meaning, function, and moral values, and has largely been limited to lexical and cognitive semantic analyses. Studies that specifically examine the rationale behind the selection of particular lexical items in proverbs—especially the word negeri - through an inquisitive semantics approach are still very limited. Therefore, this study aims to explore more deeply the meanings as well as the conceptual, cognitive, and cultural background underlying the use of the word negeri in Malay proverbs. Operationally, the data consist of Malay proverbs containing the lexicon negeri, obtained from the Pusat Rujukan Persuratan Melayu and other relevant sources. The analysis is conducted using an inquisitive semantics approach through three stages: script semantics (lexical meaning based on the Kamus Besar Bahasa Indonesia), cognitive semantics, and inquisitive semantics. In addition, the analysis considers metaphorical mapping between the source domain and the target domain to reveal the relationship between linguistic forms and their conceptual meanings. Data were collected using a note-taking technique and analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the word negeri in Malay proverbs functions not only as a geographical marker but also as a metaphor representing social concepts, collective identity, power, and the individual’s attachment to their community. The use of the word negeri reflects the Malay worldview regarding social order and the cultural values that underpin communal life.